Tingkat Pemahaman dan Dukungan Manajemen Terhadap Penerapan Green Accounting Berbasis Syariah dengan Kepedulian Lingkungan Sebagai Variabel Mediasi - Agustina Eka Harjanti; Heni Risnawati; Dian Rosita; Tuti’ Nadhifah; Ataki Zuama Nailufar; Ninik Ferawati (Jurnal Riset Akuntansi, 2026)
This journal examines the influence of the level of understanding, environmental concern, and management support on the implementation of Sharia-based green accounting in tofu MSMEs in Kudus Regency. The study uses a mixed method, combining qualitative and quantitative approaches, where the qualitative approach is used to understand the phenomena in depth, while the quantitative approach is used to empirically test the relationships between variables. The environmental concern variable is used as a mediator to analyze the indirect effect of the level of management understanding and support on the implementation of Sharia-based green accounting. The study sample consisted of 100 respondents spread throughout Kudus Regency. The results indicate that the level of management understanding and support significantly influence environmental concern. In addition, the level of understanding and concern for the environment has also been proven to affect the implementation of Sharia-based green accounting. However, management support does not have a direct impact on the implementations of Sharia-based green accounting. Environmental concern has been proven to act as a mediating variable that strengthens the influence of the level of management understanding and support for the implementation of Sharia-based green accounting. Overall, these findings confirm that improving understanding and concern for the environment is a key factors in encouraging the implementation of environmentally-based accounting practices that comply with Sharia principles in tofu MSMEs.